La Vulnerabilidad del Capital Humano en la Vialidad Lima Metropolitana y el Callao - Vicente Armas, Edgar (2017)
In the Metropolitan City of Lima and Callao, 25% (4.2 Million) of the 16 million daily trips are made through the walk mode, of this total, 49.2% have been private, 35.3% to the school and 11.9% to work; Of the total private by the way walker 52% has been to make purchases and to a lesser percentage the activities of entertainment and to go out to eat (restaurants). The ones that make use are young people (students), housewives and population of smaller economic resource. Concentrate on the places where the majority of people live in poverty, that is to say, in the outskirts of the metropolis, districts of Comas, Ate Vitarte, San Juàn de Lurigancho and others. In spite of its great importance in this way, it has become the most dangerous; Of every 100 people killed by traffic accidents 78 were pedestrians. There are other factors that condition pedestrian action such as: Insufficient pedestrian traffic; Conflict of vehicular flows with pedestrian flows in the moment of rotation to the right and left among others. N moments of amber light among others.